Variability in Essential Oil Constituents, Antioxidant Activities and Yield of Elite Small Cardamom Lines (Elettaria cardamomum Maton) Under Moisture Deficit Stress. Issue 5 (3rd September 2022) - Ankegowda, S.J.; Alagupalamuthirsolai, M.; Sivaranjani, R.; Peeran, Mohammed Faisal; Krishnamurthy, K.S.; Shivakumar, M.S.
Abstract: A field study was conducted at ICAR-Indian Institute of Spices Research, Regional Station, Madikeri, Karnataka during 2018 and 2019 to evaluate elite lines of small cardamom ( Elettaria cardamomum Maton) for capsule yield, essential oil constituents, photosynthesis and antioxidant enzyme activities under moisture stress condition. Eight small cardamom lines were selected for the study and were grown under irrigated and moisture stress conditions adopting all the package of practices. Photosynthetic gas exchange, relative water content, total soluble proteins and antioxidant enzyme activities were determined at panicle initiation stage during summer. Yield and essential oil components were recorded after harvest. The results showed that moisture stress significantly reduced the soluble protein content and stomatal conductance in the leaves thereby lowering net photosynthetic rate, thus inhibiting growth and yield. Antioxidant enzyme activities viz. catalase, peroxidase, superoxide dismutase and polyphenol oxidase were significantly influenced by moisture stress. Among the genotypes, IC584058 showed bold capsules, higher and less reduction in yield under irrigated and moisture stress condition, respectively. It is suggested that the soluble protein and antioxidant enzymes in leaves play important role in maintaining cell water content and photosynthetic gas exchange during panicle initiation stage leading to less reduction in yield under moisture deficit condition. The essential oil components of three lines namely IC584058, IC584078 and IC584090 showed drastic variation under moisture stress. Though the α-terpinyl acetate content decreased (P<0.05), the oxygenated monoterpenes significantly increased in stress tolerant genotype IC584058 which influences antioxidant and antimicrobial activities leading to plant adaptive defense mechanism under moisture.